Wellbeing in pre-service teacher education: gender and economic disparities among Cambodian student teachers - Ueno, Marie; Asakura, Takashi; Monobe, Hirofumi; Masuko, Yuuka; Ly, Kalyan; Thay, Sokheng; Say, Somaly (Frontiers in Education, 2025)
Cambodia, with a low Human Capital Index, faces various health challenges influenced by economic and sociocultural factors and advances health promotion in schools by empowering student teachers. This study investigated comprehensive health of students at Teacher Education Colleges (TECs) in Cambodia by assessing social determinants of health such as gender, financial status, and their interaction effect. A cross-sectional research design was used involving 587 fourth-year students from two TECs. Data were collected via an anonymized self-administered questionnaire covering wellbeing, psychological symptoms, social capital, and health and safety behaviors including diet and exercise habits, smoking, and alcohol consumption. Compared to male students, female students reported significantly higher psychological symptoms such as loneliness (F = 12.65, p < 0.001, η2 = 0.021). Also, female students had fewer social relationships than male students. Students with financial difficulties showed significantly lower wellbeing such as life satisfaction (F = 33.68, p < 0.001, η2 = 0.055) and had more psychological symptoms than those without difficulties. Their dietary habits were poor, and they lacked social support. No significant differences were found in the interaction terms between gender and financial status. Overall, the numbers of TEC students with smoking and drinking habits were relatively low, and social trust levels were notably low across all groups. This study emphasizes the need to support female students and students facing financial challenges by strengthening mental health care and social relationships within university, along with promoting social support systems for financially disadvantages students.